# Answer on Abstract Algebra Question for jifik

Question #35464

xy-[yz-zx-{yx-(3y-xz)-(xy-zy)}]

Expert's answer

xy-[yz-zx-{yx-(3y-xz)-(xy-zy)}]=xy-[yz-zx-{yx-3y+xz-xy+zy}]=xy-[yz-zx-yx+3y-xz+xy-zy]=xy-yz+zx+yx-3y+xz-xy+zy=-yz+zx+yx-3y+xz+zy

If commutativity holds (i.e. xy=yx) the last expression can be simplified: 2zx+yx-3y (for real numbers it is true).

If commutativity holds (i.e. xy=yx) the last expression can be simplified: 2zx+yx-3y (for real numbers it is true).

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment